Plasma neurodegeneration biomarker concentrations associate with glymphatic and meningeal lymphatic measures in neurological disorders - Per Kristian Eide; Aslan Lashkarivand; Are Pripp; Lars Magnus Valnes; Markus Herberg Hovd; Geir Ringstad; Kaj Blennow; Henrik Zetterberg (Nature Communications, 2023)
Abstract Clearance of neurotoxic brain proteins via cerebrospinal fluid (CSF) to blood has recently emerged to be crucial, and plasma biomarkers of neurodegeneration were newly introduced to predict neurological disease. This study examines in 106 individuals with neurological disorders associations between plasma biomarkers [40 and 42 amino acid-long amyloid-β (Aβ40 and Aβ42), total-tau, glial fibrillary acidic protein (GFAP), and neurofilament light (NfL)] and magnetic resonance imaging measures of CSF-mediated clearance from brain via extra-vascular pathways (proxy of glymphatic function) and CSF-to-blood clearance variables from pharmacokinetic modeling (proxy of meningeal lymphatic egress). We also examine how biomarkers vary during daytime and associate with subjective sleep quality. Plasma concentrations of neurodegeneration markers associate with indices of glymphatic and meningeal lymphatic functions in individual- and disease-specific manners, vary during daytime, but are unaffected by sleep quality. The results suggest that plasma concentrations of neurodegeneration biomarkers associate with measures of glymphatic and meningeal lymphatic function.